An application of physics: simply supported bridges made of post-tensioned concrete and structural steel beam (2022)
Bridges represent an important application of physics capable of solving real transportation problems. Knowledge of convenience of different mechanical solutions when analyzing and designing bridge is needed. For these reasons, this work is focused on the study of convenience of using two types of bridges. Simply supported short-medium span bridges (30 m to 45 m) are usually excessively long when choosing reinforced concrete solutions and usually short for other types of structures such as cable-stayed or cantilever bridges. The suitability of simply supported bridges leads to the need of studying their cost benefit ratios. This work studies the cost benefit ratio for post-tensioned concrete beams and structural steel girders in simply supported straight bridges. Eight models built of type I sections were used in both cases to analyze the bridges using a software based on the stiffness method. Span of each bridge was set to 30 m, 35 m, 40 m, and 45 m. The convenience of each type of bridge was done comparing the total and the cost per linear meter of each solution (post-tensioned and structural steel). Comparison was done using material consumption, labor, and construction processes costs only. Also, allowable vertical displacement given by current bridge design standards was verified